The association of limbic system activation with dream, bad dream and nightmare generation - King, Warren (Department of Psychology, 2018)
Despite the fact that nightmares occur with regularity in the general population, most previous research has focused on clinical samples, and the genesis of idiopathic nightmares remains poorly understood. The aim of the present research was therefore to investigate the neuropsychological mechanisms of idiopathic bad dream and nightmare generation, with a particular focus on the limbic system. High versus low levels of limbic activation and its effect on the frequency of dream, bad dream, and nightmare recall, characteristics, and content were investigated using retrospective and prospective measures. Psychosocial stress – a phenomenon which increases activity in the limbic system – and its relationship to bad dreams and nightmares was also investigated, using questionnaires and a prospective dream diary study. Oral contraceptive use was included as a moderator variable as previous research has indicated that this may temper reactions to stress. The general hypothesis that greater activation of the limbic system results in a greater frequency of recall of bad dreams and nightmares, and also results in more negative dream content, was confirmed. It was also found that external factors which increase limbic activation such as psychosocial stress lead to a greater recall of bad dreams and nightmares. Although oral contraceptive use did not moderate the relationship between stress and bad dream and nightmare recall frequency, more generally positive dream content was found in users of oral contraceptives compared to non-users. Taken together, the results of the studies indicate that similar neuropsychological mechanisms may underlie the formation of idiopathic nightmares and nightmares in clinical conditions, and also that increased levels of limbic activation may result most commonly in negative dream content.